(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to describe the level of member satisfaction with service quality At Defilla Sport based on five aspects of service quality, tangible, reliability, responsiveness, assurance, and emphaty. The method used is quantitative descriptive research with a survey approach. The population of this study consists of all active member at Defilla sport. The sample for this study consists of active members aged 18-40 years who are willing to participate as respondents. Data was obtained from 30 respondents who are active members of Defilla Sport. The data was analyzed descriptive to determine the distribution of satisfaction based on each service dimension. The results of the study show that 20 respondents 67 were satisfied with the service provided, while 7 respondents 23 were dissatisfied, and 3 respondents 10 were very dissatisfied. Base on this study, it can be concluded that overall, the quality of service at Defilla Sport is considered good and capable of meeting the expectation of the majority of members, although improvements are still needed in terms of physicals aspects and supporting facilities. This study provides insights for Defilla Sport management to continue improving service quality to maintain member satisfaction and loyalty.